A Comparison of Mathematics Teachers Assessment Practices Between Public and Private Schools in District Sargodha - Muhammad Zafar Iqbal, Ghulam Haider, Jahan Ara Shams (JCTE, 2023)
Examining mathematics teachers’ practices in assessing students’ performance was the major concern of this research study. A survey method was applied within descriptive research design. The population of the study was all the 6th and 7th grade mathematics teachers teaching in elementary schools of district Sargodha. The sample of the study was one hundred and forty mathematics teachers of tehsil Shahpur of district Sargodha.